Chromosome analysis in a case of a plutonium contaminated wound. (30th March 2017) - Tawn, E Janet; Curwen, Gillian B; Riddell, Anthony E; Lloyd, David C; Ainsbury, Elizabeth A
Abstract: Chromosome analysis of peripheral blood lymphocytes was undertaken over a 10 year period following an intake of plutonium through a hand wound. Frequencies of cells with unstable complex aberrations remained high throughout this time, probably reflecting direct exposure of lymphocytes as they passed plutonium which had transferred to regional lymph nodes. Analysis at the final sampling time also revealed cells with stable aberrations at a much higher frequency relative to the number of unstable cells than expected from direct exposure, and is therefore most likely to be reflecting exposure to lymphocyte precursor cells from plutonium that has become deposited on bone surfaces.